ANALISIS PENENTUAN NILAI INTRINSIK DAN TARGET PRICE PADA SAHAM LQ-45 - , Tonny Wijaya Setiadi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research identified analysis method to concluded intrinsic value using EPS projection and PE ratio. This research also explained how to obtain target price using technical analysis method. The conclusion of this research identified that each methods can be implemented at stock exchange. There are nine stock objects with the biggest capitalization that been studied in this research using financial reports period 2005-2010 and historical data period 2008-2010.